Kesetaraan gender pada anak di keluarga islam - Setyaningsih, Diyah (Universitas Cokroaminoto Yogyakarta, 2021)
The purpose of this article is to find out how children's rights and gender equality exist in Indonesia. The results show that parents are the main figures in the formation of the basis of Gender Equality. In its implementation, parents need full support from various parties. Lack of socialization on how work systems with a gender equality perspective work together with a child's rights perspective. But also good parenting is the most basic thing. Currently, the gender equality movement in Indonesia is in its fourth level. At this level the role of Muslims is more dominant. This also shows that gender equality is part of Islamic teachings.